Assessment of Building Compactness at Initial Design Stage of Single-Family Houses - Edwin Koźniewski (Energies)
The paper is the culmination of research on geometric aspects of assessing the energy demand of a single-family house. In a recent study, two collections of single-family houses were analyzed: (a) a collection of 21 with outlines assumed a priori so that the building area was constant (which is not achievable in practice) and (b) a collection of 33 real buildings, recently designed by the Polish design studio Galeria Domów. These examples show the functioning of the indicators analyzed by the author in earlier papers and indicate the <semantics>RCsq</semantics> indicator that best reflects the assessment of building compactness in percentage points in relation to the ideal shape of the building plan, which is a square. The <semantics>RCsq</semantics> index is economically expressed by only two parameters, namely the base area <semantics>Af</semantics> and the building outline perimeter <semantics>P</semantics>, and therefore is easy to implement in the BIM system and at the same time covers high-rise buildings. As it turned out, the tested buildings from Galeria Domów have very good geometric and therefore energy efficiency. The above-mentioned indicator also highlights the advisability of analyzing the heated part in addition to the standard full-contour analyses.